2023
DOI: 10.7759/cureus.42338
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of COVID-19 on Breast Cancer Screenings in an Underserved Urban Population and the Screening Access of Value for Essex Program’s Efforts to Control the Damage

Abstract: Objective: This study aims to examine the impact of the COVID-19 pandemic on breast cancer screening in an underserved population, identify patient barriers, and discuss strategies to promote the importance of screening. Methods/operations: The Rutgers New Jersey Medical School Screening Access of Value for Essex (SAVE) program delivers cancer prevention services to the most vulnerable population in Essex County, New Jersey. The SAVE program was shut down from March 2020 to June 2020 due to COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…This surge is seen especially after the resolution of the COVID-19 pandemic and more specifically in underserved communities where an uptick in imaging studies like breast cancer screenings was observed. Essex County, New Jersey (NJ), is home to a large underserved community that observed a significant increase in the number of screening mammograms following the COVID-19 shutdown [8]. Without a sufficient supply of radiologists to read these screening mammograms in a timely manner, patient outcomes could be severely affected if a diagnosis were delayed or missed [9].…”
Section: Introductionmentioning
confidence: 99%
“…This surge is seen especially after the resolution of the COVID-19 pandemic and more specifically in underserved communities where an uptick in imaging studies like breast cancer screenings was observed. Essex County, New Jersey (NJ), is home to a large underserved community that observed a significant increase in the number of screening mammograms following the COVID-19 shutdown [8]. Without a sufficient supply of radiologists to read these screening mammograms in a timely manner, patient outcomes could be severely affected if a diagnosis were delayed or missed [9].…”
Section: Introductionmentioning
confidence: 99%